Phylogenomic discernments into Anaerolineaceae thermal adaptations and the proposal of a candidate genus Mesolinea - Bedoya-Urrego, Katherine; Alzate, Juan F. (Frontiers in Microbiology, 2024)
This study delves into the evolutionary history of Anaerolineaceae, a diverse bacterial family within the Chloroflexota phylum. Employing a multi-faceted approach, including phylogenetic analyses, genomic comparisons, and exploration of adaptive features, the research unveils novel insights into the family's taxonomy and evolutionary dynamics. The investigation employs metagenome-assembled genomes (MAGs), emphasizing their prevalence in anaerobic environments. Notably, a novel mesophilic lineage, tentatively named Mesolinea, emerges within Anaerolineaceae, showcasing a distinctive genomic profile and apparent adaptation to a mesophilic lifestyle. The comprehensive genomic analyses shed light on the family's complex evolutionary patterns, including the conservation of key operons in thermophiles, providing a foundation for understanding the diverse ecological roles and adaptive strategies of Anaerolineaceae members.